Trade, Liners, Treaties. Piedmontese Consuls in the Long Atlantic, 1819-1838 - Marco Mariano (Centre de Recherches sur les Mondes Américains, 2012)
The article discusses the role played by Piedmontese consuls in the US to facilitate the economic and political integration of Piedmont in the Atlantic world of the post-Restoration years. It shows that their effort to promote commercial exchanges with the United States often found strong local resistance but, nonetheless, helped undermine protectionist policies and international isolation in the following decades. Furthermore, their quest for Atlantic integration was the ultimate outcome of flexible adaptations and creative interpretations of the official policies formulated by the political and diplomatic establishment. This case study, then, prompts further investigation on how consular networks in Europe and the Americas worked as a connective tissue between state actors and transnational forces in the shaping of commercial and political relations across the Atlantic since the first half of the 19th century.